CRM 2.0 within E-Health Systems: Towards Achieving Health Literacy & Customer Satisfaction - Anshari, Muhammad; Almunawar, Mohammad Nabil; Low, Patrick Kim Cheng (IJID (International Journal on Informatics for Development), 2012)
Customer Relationship Management (CRM) within healthcare organization can be viewed as a strategy to attract new customers and retaining them throughout their entire lifetime of relationships. At the same time, the advancement of Web technology known as Web 2.0 plays a significant part in the CRM transition which drives social change that impacts all institutions including business and healthcare organizations. This new paradigm has been named as Social CRM or CRM 2.0 because it is based on Web 2.0. We conducted survey to examine the features of CRM 2.0 in healthcare scenario to the customer in Brunei Darussalam. We draw the conclusion that the CRM 2.0 in healthcare technologies has brought a possibility to extend the services of e-health by enabling patients, patients families, and community at large to participate more actively in the process of health education; it helps improve health literacy through empowerment, social networking process, and online health educator. This paper is based on our works presented at ICID 2011.